Extruding Plastics - A Practical Processing Handbook - Rosato, D.V. (Chapman & Hall, 2011)
This book, with its practical industry reviews, is a unique handbook (the first of its kind) that covers over a thousand of the potential combinations of basic variables or problems with solutions that can occur from up-stream to down-stream equipment.